Perturbation of the Dimer Interface of Triosephosphate Isomerase and its Effect on Trypanosoma cruzi - Olivares-Illana, Vanesa (Public Library of Science, 2007)

(untitled)
BACKGROUND: Chagas disease affects around 18 million people in the American continent. Unfortunately, there is no satisfactory treatment for the disease. The drugs currently used are not specific and exert serious toxic effects. Thus, there is an urgent need for drugs that are effective. Looking for molecules to eliminate the parasite, we have targeted a central enzyme of the glycolytic pathway: triosephosphate isomerase (TIM). The homodimeric enzyme is catalytically active only as a dimer. Because there are significant differences in the interface of the enzymes from the parasite and humans, we searched for small molecules that specifically disrupt contact between the two subunits of the enzyme from Trypanosoma cruzi but not those of TIM from Homo sapiens (HTIM), and tested if they kill the parasite. METHODOLOGY/PRINCIPAL FINDINGS: Dithiodianiline (DTDA) at nanomolar concentrations completely inactivates recombinant TIM of T. cruzi (TcTIM). It also inactivated HTIM, but at concentrations around 400 times higher. DTDA was also tested on four TcTIM mutants with each of its four cysteines replaced with either valine or alanine. The sensitivity of the mutants to DTDA was markedly similar to that of the wild type. The crystal structure of the TcTIM soaked in DTDA at 2.15 Å resolution, and the data on the mutants showed that inactivation resulted from alterations of the dimer interface. DTDA also prevented the growth of Escherichia coli cells transformed with TcTIM, had no effect on normal E. coli, and also killed T. cruzi epimastigotes in culture. CONCLUSIONS/SIGNIFICANCE: By targeting on the dimer interface of oligomeric enzymes from parasites, it is possible to discover small molecules that selectively thwart the life of the parasite. Also, the conformational changes that DTDA induces in the dimer interface of the trypanosomal enzyme are unique and identify a region of the interface that could be targeted for drug discovery.